2020
DOI: 10.1080/03009742.2020.1753808
|View full text |Cite
|
Sign up to set email alerts
|

Elevated adiponectin predicts the development of rheumatoid arthritis in subjects with obesity

Abstract: Objective The aim of the current study is to determine whether baseline serum adiponectin levels predict the development of rheumatoid arthritis (RA). Method The current report includes 3693 individuals from the Swedish Obese Subjects (SOS) study. The original SOS study is a longitudinal non-randomized controlled study aiming to assess the effect of bariatric surgery on obesity-related mortality and morbidity. Participants included in the present report had adiponectin measurement available at baseline and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
(53 reference statements)
4
15
0
1
Order By: Relevance
“…Plasma levels of adiponectin have been shown to associate with levels of circulating pro-inflammatory cytokines, i.e., IL-2, IL-6, IL-9, and granulocyte-macrophage colony-stimulating factor (GM-CSF) in relatives of RA patients that had a high-risk autoantibody profile ( 24 ). Together with our finding that an increase in serum adiponectin levels predicts the development of RA, this suggests that adiponectin plays a role in the initiation of the disease ( 16 ). In the current study, we aimed to determine if adiponectin is able to induce pro-inflammatory responses in cells involved in the pathogenesis of RA, but collected from subjects without any known inflammatory disease.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Plasma levels of adiponectin have been shown to associate with levels of circulating pro-inflammatory cytokines, i.e., IL-2, IL-6, IL-9, and granulocyte-macrophage colony-stimulating factor (GM-CSF) in relatives of RA patients that had a high-risk autoantibody profile ( 24 ). Together with our finding that an increase in serum adiponectin levels predicts the development of RA, this suggests that adiponectin plays a role in the initiation of the disease ( 16 ). In the current study, we aimed to determine if adiponectin is able to induce pro-inflammatory responses in cells involved in the pathogenesis of RA, but collected from subjects without any known inflammatory disease.…”
Section: Introductionsupporting
confidence: 76%
“…As a support for this hypothesis, adiponectin has been shown to induce the production of IL-6, TNF, CXCL1, and CXCL8 in human lymphocytes from healthy subjects ( 10 ), and IL-6 and CXCL8 in FLS collected from subjects with RA ( 20 ). We have also recently shown that increased circulating adiponectin levels precede the development of RA in subjects with obesity, suggesting that adiponectin could play a role in the early phases of disease pathogenesis ( 16 ). The current study shows that adiponectin stimulates the production of a wide range of pro-inflammatory chemokines and cytokines in PBMCs and FLS collected from non-inflamed subjects, thus suggesting that adiponectin is able to initiate pro-inflammatory responses in healthy cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, subcutaneous adipose tissue from RA patients produced more adiponectin compared to OA patients and correlated with disease activity and disease duration in these patients [ 49 ]. Along this line, an increased risk for obese subjects with high serum adiponectin levels at baseline to develop RA, specifically with high adiponectin and CRP levels, was recently described in a study during a follow-up for up to 29 years [ 50 ]. The response to anti-TNF-alpha treatment seems to be associated with better improvement in patients with higher adiponectin levels at baseline [ 51 ].…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…Collectively, it was reported that adiponectin is associated with the erosive process ( 49 53 ). Finally, in a Swedish cohort of obese subjects, elevated levels of adiponectin were associated with the development of RA, independently of CRP and levels of smoking (hazard ratio: 1.7 [95% CI: 1.12-2.6]) ( 60 ).…”
Section: Adipokines In Rheumatoid Arthritismentioning
confidence: 99%